Efektivitas Penggunaan Diorama AR terhadap Pemahaman Konsep Siswa Kelas V dalam Materi Makhluk Hidup - Hujiroh, Shofa; khoerunnisa, Vina; hastuti, Sri; Heryadi, Yadi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to evaluate the effectiveness of Augmented Reality (AR) Diorama media in improving the understanding of the concept of grade V students towards living things in learning science. The background of this research is based on the need for technology-based learning innovations that are able to overcome the limitations of conventional media in conveying abstract concepts. This study uses a descriptive qualitative approach with data collection techniques through observation, semi-structured interviews, and questionnaires. The research subjects consisted of 28 grade V students and classroom teachers at SDN 2 Parung Sari. The results showed that the use of AR Diorama significantly increased students' enthusiasm, participation, and concept understanding. Interactive 3D visualization allows students to explore the body structure of living things in detail, making it easier to connect theory with visual reality. Interviews with students and teachers show that this medium not only helps with the cognitive aspect, but also fosters students' interest, curiosity, and courage to express their opinions. The results of the questionnaire strengthened this finding, where most students stated that the use of AR in understanding the material was very helpful. This study concludes that AR Diorama is an effective medium to be applied in IPAS learning, especially in helping students understand abstract material in a more concrete, fun, and meaningful way.